2002
DOI: 10.1002/mus.10159
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiologic parameters and symptoms in chronic renal failure

Abstract: We studied: (1) the sensitivity of various neurophysiologic parameters in the diagnosis of uremic polyneuropathy, (2) the relationship between subjective symptoms and neurophysiologic parameters, and (3) the effect of a single hemodialysis on the neurophysiologic parameters in 21 patients undergoing hemodialysis. The following parameters were studied: sensory and motor nerve conduction, including F-wave parameters; vibration detection thresholds; and thermal thresholds. The clinical findings and subjective sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
52
3
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 27 publications
8
52
3
4
Order By: Relevance
“…Neuropathological studies in patients with UP have demonstrated predominant axonal involvement with secondary segmental demyelination [7,8]. These studies are supported by neurophysiological examinations [9][10][11]. Routine neurophysiological nerve conduction studies (NCS) and needle examinations evaluate large-diameter myelinated fibers only and are insufficient to detect a dysfunction of small-diameter nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropathological studies in patients with UP have demonstrated predominant axonal involvement with secondary segmental demyelination [7,8]. These studies are supported by neurophysiological examinations [9][10][11]. Routine neurophysiological nerve conduction studies (NCS) and needle examinations evaluate large-diameter myelinated fibers only and are insufficient to detect a dysfunction of small-diameter nerve fibers.…”
Section: Introductionmentioning
confidence: 99%
“…CSP is a complementary method to conventional NCS and is very useful in the study of small-diameter nerve fiber function. However, quantitative sensory testing of small and unmyelinated nerve fibers is not widely performed in neurophysiological units [10,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…These insights were provided through the use of novel nerve excitability techniques, a clinical method that enables indirect assessment of ion channels, pumps and exchangers that are involved in the process of nerve impulse conduction (8). These techniques have proven particularly useful in detecting changes in peripheral nerve function in patients with chronic kidney disease (CKD), with previous studies demonstrating prominent changes in CKD patients receiving renal replacement therapies (9,10), changes that are undetectable using routine nerve conduction studies (11). The present study was undertaken to investigate the mechanisms underlying neurotoxicity in patients receiving immunosuppressive treatment following renal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…This is apparent with the metabolic neuropathies, particularly diabetic and uremic neuropathy. 5,16,17,35,36 This predilection of metabolic disorders to affect preferentially lower-limb nerves has been related to the fact that these nerves are longer, although the basis for such length-dependent involvement has yet to be clearly established. 1,36,50 Adapting nerve excitability techniques to assess lower-limb nerve function is therefore timely.…”
mentioning
confidence: 97%